Community-based programs for youth with mental health conditions: a scoping review and practical implications - Tuaf, Hila; Orkibi, Hod (Frontiers in Public Health, 2023)
Background: approximately 14% of all adolescents globally cope with mental health conditions. However, community-based psychosocial services for adolescents with mental health conditions are scarce and under-researched. Scant scholarly attention has been paid to leisure and/or social activities in community-based rehabilitation services for adolescents with mental health conditions. Objectives: to begin to fill this gap, we chose a bottom-up framework to probe the following questions: Which community-based programs for adolescents with mental health conditions exist worldwide? What common characteristics do they present? What is their range of services? Method: we systematically searched three leading academic databases, reference lists, and worldwide websites in English. Eligibility criteria: programs with information in English that provide services in a community setting, service content that includes leisure and/or social activities, cater to users aged 10-18, and content explicitly targets adolescents with mental health conditions. Results: twenty-seven psychosocial programs that provide leisure and/or social activities and encourage the promotion of adolescent mental health in the community were identified. We mapped and categorized the programs into three groups: integrated recovery, leisure recovery, and advocacy recovery. Conclusions: practical implications for implementation are suggested based on the findings. Specifically, service providers should attend to the psychological needs of adolescents by prioritizing peer interaction and offering suitable social and leisure activities. These activities can also boost adolescent participation in community-based rehabilitation programs and address the treatment gap. Comprehensive studies and uniform terminology in the field are needed.